The effect of antenatal care examinations on early detection of high-risk pregnancy - Parningotan Simanjuntak; Nopalina Suyanti Damanik; Sri Rezeki; Debby Chintya Yun; Magdalena Barus; Desi Ulina Sipayung (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: A high-risk pregnancy is a pregnancy that can endanger the health of the mother and fetus due to complications, both pre-existing and emerging during pregnancy, such as hypertension, diabetes, preeclampsia, anemia, and infection. Antenatal care (ANC) examinations play a crucial role in early detection of high-risk pregnancies so that complications can be prevented or managed early. Purpose: To analyze the effect of Antenatal Care examinations on early detection of high-risk pregnancies. Method: This study used a quantitative design with an analytical survey approach. The study was conducted from February to June 2025 at Efarina Karo Hospital. The study population was all pregnant women undergoing ANC examinations, using a purposive sampling technique. Data were analyzed using the Chi-Square test with a 95% confidence level (p-value = 0.05). Results: The results showed that the majority of respondents (30 respondents) underwent a complete ANC examination. Early detection of high-risk pregnancies was found in 27 respondents (60.0%). Pregnant women who underwent a complete ANC examination were more likely to have high-risk pregnancies detected, namely 22 respondents (73.3%). The chi-square test showed a p-value of 0.012 (p < 0.05). Conclusion: There is a significant influence between antenatal care (ANC) examinations and the early detection of high-risk pregnancies. Comprehensive ANC examinations are crucial for improving early detection and preventing pregnancy complications.